Makna Kultural Benda-benda Bersejarah Peninggalan Kesultanan Kutaringin: Sebuah Pendekatan Semantik Pedagogis - Dina Mardiana; Iwan Fauzi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
The Kutaringin Sultanate is one of the most magnificent heritages of the Islamic Kingdom in Indonesia, located in West Kotawaringin Regency, Central Kalimantan Province. As a cultural product, these historical objects from the Kutaringin Sultanate are worthy of being documented through cultural semiotic study and developed into a lecturing model of language and literature containing of artifact discourses based on local wisdom. The purpose of this study is to describe the cultural meanings of historical objects from the Kutaringin Sultanate and their implications in language and literature lectures at the university. The implementation of this research used a qualitative method with two approaches, both were the lexical semantic approach and the pedagogical approach. The result of this study found 39 historical objects that can be culturally interpreted and developed into a lecturing model of language and literature containing artifact discourses based on local wisdom for the university students.